2006
DOI: 10.1021/ol061856x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Stable 2H-Pyran-5-carboxylates via a Catalyzed Propargyl-Claisen Rearrangement/Oxa-6π Electrocyclization Strategy

Abstract: [reaction: see text] The application of easily accessed propargyl vinyl ethers for the synthesis of monocyclic 2H-pyrans was achieved. Under the reaction conditions, highly substituted heterocycles were obtained in moderate to excellent yields. The one-pot sequence proceeds via a Ag(I)-catalyzed propargyl-Claisen rearrangement, followed by a base-catalyzed isomerization, and 6pi-oxaelectrocyclization, leading to the formation of stable 2H-pyrans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…As a result of screening the solvent effect, we found that the yield of 3a was improved to 71 % by use of THP for 24 h, compared with other solvents such as THF (61 %), CH 2 Cl 2 (60 %), and toluene (59 %) (Table 1, entries 4, [8][9][10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of screening the solvent effect, we found that the yield of 3a was improved to 71 % by use of THP for 24 h, compared with other solvents such as THF (61 %), CH 2 Cl 2 (60 %), and toluene (59 %) (Table 1, entries 4, [8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…In general, the hydrogenation occurred selectively on a double bond at the C3,4 positions [8] and the cis isomers were predominant in the C2 alkyl derivatives, namely, 21a and 23, whereas the C2 phenyl derivative 18 produced a mixture of cis/trans isomers 22. [18] Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism has been supported by the isolation in two cases of the conjugated dienone (69). 77 Alkynyl propargyl sulfides have been shown to rearrange on heating by a [3,3]-sigmatropic rearrangement-four-electron electrocyclic ring closure sequence. When both alkynes bear terminal substituents, the product 4-methylenecyclobutenethiones have been found to be isolable in moderate to good yields, and it has been shown that an intermediate allenylthioketene can be trapped using diethylamine.…”
Section: Tandem Pericyclic Rearrangementsmentioning
confidence: 93%
“…The (thio)acetal group has been shown to be required for the reaction to proceed, and it has been suggested that hyperconjugative interactions between the O or S lone pairs and the C-H σ * orbital weaken the C-H bond and allow the hydride shift to occur. Derivatives of 3-allyl-4-(dialkylallenyl)furan-2(5H )-one (77) have been shown to rearrange on heating to give fused bicyclic cyclooctatriene derivatives (78) in moderate to excellent yields. Although the products are formally those of an ene reaction between allyl and allene groups, two alternative mechanisms have been proposed: either direct [1,5]-hydrogen shift followed by eight-electron electrocyclization, or initial 2 + 2-cycloaddition followed by [1,5]-hydrogen shift and six-electron electrocyclic ring opening, as shown in Scheme 14.…”
Section: Tandem Pericyclic Rearrangementsmentioning
confidence: 99%